PRIMARY SCHOOL TEACHERS’ PERCEPTIONS OF PROJECT-BASED LEARNING IMPLEMENTATION IN CIVIC EDUCATION: OPPORTUNITIES AND PEDAGOGICAL CHALLENGES - Novi Eka Saputri; Saddam Fathurrachman (El Midad, 2025)
This study investigates the relationship between primary school teachers’ perceptions and the implementation of Project-Based Learning (PjBL) in Civic Education (PKn) within the context of Indonesia’s Kurikulum Merdeka. The research was conducted using a quantitative survey approach to analyze how teachers’ attitudes and understanding influence their classroom practices. Data were collected from 50 elementary school teachers in North Lampung Regency, selected through random sampling. A structured Likert-scale questionnaire consisting of ten items was administered, and data were analyzed using SPSS version 25. The instrument demonstrated acceptable validity (r > 0.279) and reliability (Cronbach’s ? = 0.770). The results of simple linear regression indicated a significant positive relationship between teachers’ perceptions and PjBL implementation (? = 0.764; p < 0.05), with a determination coefficient (R²) = 0.370, meaning that teachers’ perceptions can explain 37% of the variance in implementation. These findings confirm that teachers’ cognitive and affective readiness substantially affect the adoption of innovative pedagogies in Civic Education. Theoretically, this study reinforces social cognitive and constructivist learning frameworks, while practically, it highlights the need for systematic professional development and institutional support to enhance teacher capacity. The study contributes novelty by focusing on elementary Civic Education, a rarely explored field in PjBL research, and emphasizes the ethical and digital implications of project-based civic learning in the 21st-century classroom.